Original paper: Efficacy and safety analysis of insulin degludec/insulin aspart compared with biphasic insulin aspart 30: A phase 3, multicentre, international, open-label, randomised, treat-to-target trial in patients with type 2 diabetes fasting during Ramadan. (January 2018) - Hassanein, Mohamed; Echtay, Akram Salim; Malek, Rachid; Omar, Mahomed; Shaikh, Shehla Sajid; Ekelund, Magnus; Kaplan, Kadriye; Kamaruddin, Nor Azmi
Highlights: IDegAsp had similar glycaemic efficacy to BIAsp 30 before, during and after Ramadan. During Ramadan, IDegAsp achieved significantly lower pre- iftar SMPG vs BIAsp 30. IDegAsp caused significantly less overall and nocturnal hypoglycaemia vs BIAsp 30. During Ramadan, IDegAsp had significantly less daytime hypoglycaemia vs BIAsp 30. IDegAsp and BIAsp 30 are suitable for patients on insulin who choose to fast. Abstract: Aims: To compare the efficacy and safety of insulin degludec/insulin aspart (IDegAsp) and biphasic insulin aspart 30 (BIAsp 30) before, during and after Ramadan in patients with type 2 diabetes mellitus (T2DM) who fasted during Ramadan. Methods: In this multinational, randomised, treat-to-target trial, patients with T2DM who intended to fast and were on basal, pre- or self-mixed insulin ± oral antidiabetic drugs for ≥90 days were randomised (1:1) to IDegAsp twice daily (BID) or BIAsp 30 BID. Treatment period included pre-Ramadan treatment initiation (with insulin titration for 8–20 weeks), Ramadan (4 weeks) and post-Ramadan (4 weeks). Insulin doses were reduced by 30–50% for the pre-dawn meal ( suhur ) on the first day of Ramadan, and readjusted to the pre-Ramadan levels at the end of Ramadan. Hypoglycaemia was analysed as overall (severe or plasma glucose <3.1 mmol/L [56 mg/dL]), nocturnal (00:01–05:59) or severe (requiring assistance of another person). Results: During the treatment period, IDegAsp (n = 131) had significantly lower overall and nocturnal hypoglycaemia rates with similar glycaemic efficacy, versus BIAsp 30 (n = 132). During Ramadan, despite achieving significantly lower pre- iftar (meal at sunset) self-measured plasma glucose (estimated treatment difference: −0.54 mmol/L [−1.02; −0.07]95% CI, p  = .0247; post hoc ) with similar overall glycaemic efficacy, IDegAsp showed significantly lower overall and nocturnal hypoglycaemia rates versus BIAsp 30. Conclusions: IDegAsp is a suitable therapeutic agent for patients who need insulin for sustained glucose control before, during and after Ramadan fasting, with a significantly lower risk of hypoglycaemia, versus BIAsp 30, an existing premixed insulin analogue.